ПОРІВНЯЛЬНИЙ АНАЛІЗ ДИНАМІЧНИХ ХАРАКТЕРИСТИК SI-MOSFET, SIC-MOSFET ТА SI-IGBT ТРАНЗИСТОРІВ - Ковбаса, С.М.; Вербовий, Ю.В.; Коломійчук , Є.В. (Інститут електродинаміки НАН України, Київ, 2025)
This work is dedicated to the practical determination and comparison of the dynamic characteristics of silicon (Si) MOSFET, silicon carbide (SiC) MOSFET, and silicon IGBT when switching an active-inductive load, which is the most used mode of operation in electric drives and power converters. The main advantages and challenges associated with the use of high-speed switches in real applications are discussed.  The methodology of the Double-Pulse Test (DPT), a widely used method for experimental determining the dynamic characteristics of MOSFET and IGBT is presented. An experimental setup for conducting this test was designed and manufactured. The transistors were tested under identical voltage conditions for different switching currents. The analysis of the experimental data has demonstrated that, under equal conditions, SiC-MOSFET provides the lowest switching losses, making it the most suitable for applications which demand high-frequency PWM. It is shown that due to the lowest turn-on and turn-off delays (compared to other types of transistors considered) SiC-MOSFET can potentially reduce the converter's dead-time, this fact, in turn, improves the inverter's dynamic performance and simplifies or even eliminates the need for dead-time compensation algorithms. References 27, figures 13, tables 3.